The use of geoinformation in rural and urban-rural gminas of Zgierz poviat – a pilot survey - Feltynowski, Marcin (Bulletin of Geography. Socio-economic Series, 2013)
The use of geoinformation becomes more and more common due to the implementation of EU law to the regulations of individual member states. The opportunity of faster implementation of spatial information systems and geoinformation is possible thanks to the popularisation of knowledge concerning the ways of using spatial information. The pilot survey was conducted in rural and urban-rural gminas of Zgierz poviat (administrative unit of the 2nd order). The aim of the survey was to check if the officials in small gminas have knowledge and access to geoinformation. A part of the research was the identification of the sources of obtaining knowledge and sources of obtaining spatial data. The consequence of such an attitude was, as well, to prove in which areas of territorial unit activity geoinformation is used. An important element of the study was self-assessment of the knowledge level of the officials about geoinformation and spatial information systems. The study helped to determine if there is a knowledge gap in Polish gminas. The analyses allow for indicating the level and areas of geoinformation usage by the local authorities.